2019
DOI: 10.1136/postgradmedj-2019-136398
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependence of NIHSS in predicting functional outcome of patients with acute ischemic stroke treated with intravenous thrombolysis

Abstract: ObjectivesThe National Institute of Health Stroke Scale (NIHSS) is a predictor for the prognosis of acute ischaemic stroke (AIS) and its prediction is time-dependent. We examined the performance of NIHSS at different timepoints in predicting functional outcome of patients with thrombolysed AIS.MethodsThis prospective study included 269 patients with AIS treated with recombinant tissue plasminogen activator (rt-PA). Unfavourable functional outcome was defined as modified Rankin Scale score 4–6 at 3 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
2
25
0
5
Order By: Relevance
“…In another study, significant, male gender and NIHSS were the significant predictors of functional outcome at 3 months (10) . Similar conclusions were reported by the studies of Bhaskar et al (11) Wu et al (12) Thatikonda et al (13) . Of note, the Egyptian study of Mohamed et al (14) , older age, presence of diabetes and dyslipidemia was significant predictors of poor outcome reported in 50.0 % of patients in that 157 patients study.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, significant, male gender and NIHSS were the significant predictors of functional outcome at 3 months (10) . Similar conclusions were reported by the studies of Bhaskar et al (11) Wu et al (12) Thatikonda et al (13) . Of note, the Egyptian study of Mohamed et al (14) , older age, presence of diabetes and dyslipidemia was significant predictors of poor outcome reported in 50.0 % of patients in that 157 patients study.…”
Section: Discussionsupporting
confidence: 90%
“…The level of the NIHSS score can reflect the clinical situation of the patient with ACI more intuitively. The NIHSS score reveals the extent of neurological damage and is usually used to evaluate the efficacy of patients with ACI after therapy ( Wu et al., 2019 ). In this study, twenty-two studies with 2020 patients were assessed using the NIHSS score.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted the outcome of AIS patients using only one or two factors, particularly the NIHSS score and age, which have been recognized as the most direct contributors to patient outcome (20). The NIHSS score indicates the degree of neurological function damage and is frequently used to determine the severity of the patient's condition on admission (21). The majority of studies have used the NIHSS score as an important predictive factor for patient outcome following AIS; however, the outcome threshold frequently differed among these studies (21).…”
Section: Discussionmentioning
confidence: 99%
“…The NIHSS score indicates the degree of neurological function damage and is frequently used to determine the severity of the patient's condition on admission (21). The majority of studies have used the NIHSS score as an important predictive factor for patient outcome following AIS; however, the outcome threshold frequently differed among these studies (21). The present study also indicated that the NIHSS score on admission was the strongest factor associated with patient outcome, which was consistent with the conclusions of previous studies.…”
Section: Discussionmentioning
confidence: 99%